The technology transfer ecosystem in academia. An organizational design perspective. (April 2019) - Good, Matthew; Knockaert, Mirjam; Soppe, Birthe; Wright, Mike
Abstract: University technology transfer has emerged as an important and standalone research field over the past few decades. Given the great challenges that are involved with transferring science to the market, many universities have established technology transfer offices, science parks, incubators, and university venture funds – an organizational assemblage labelled the technology transfer (TT) ecosystem. By reviewing the extant literature on the TT ecosystem and its components, this paper aims at providing an understanding of the organizational design of the TT ecosystem. Surprisingly, the results of this review show that research considering this ecosystem as a whole is largely lacking. Specifically, the literature on the topic can be typified as atomistic, with a wide range of studies on the various TT components and a dearth of research studying holistically the wider knowledge transfer ecosystem that reflects the evolution and impact of academic entrepreneurship. Consequently, this paper presents an organizational design framework that sets out a future research agenda for studies taking a holistic approach. Highlights: We review the literature on the technology transfer ecosystem and components. Research considering the technology transfer ecosystem as a whole is scant. Overlaps and differences exist in the organizational design of its components. We call for a holistic instead of atomistic approach into this ecosystem. We present a research agenda for studying the technology transfer ecosystem holistically.